Roux-en-Y gastric bypass and laparoscopic sleeve gastrectomy effects on obesity comorbidities: A systematic review and meta-analysis - Alghamdi, Salah; Mirghani, Hyder; Alhazmi, Khalid; Alatawi, Amirah M.; Brnawi, Haneen; Alrasheed, Tariq; Badoghaish, Waleed (Frontiers in Surgery, 2022)
Roux-en Y gastric bypass (LRYGB) and laparoscopic sleeve gastrectomy (LSG) are the most commonly used bariatric procedures. There is an increasing awareness about a comorbidity-based indication for bariatric surgery regardless of weight (metabolic surgery). The best operation to mitigate obesity-associated comorbidities is a matter of controversy. This review is aimed at comparing LRYGB and LSG for the treatment of diabetes, hypertension, dyslipidemias, obstructive sleep apnea (OSA), and gastroesophageal reflux (GERD). We searched PubMed, MEDLINE, SCOPUS, Web of Science, and Cochrane library for articles comparing these two commonly used bariatric approaches. We identified 2457 studies, 1468 of which stood after the removal of duplications; from them, 81 full texts were screened and only 16 studies were included in the final meta-analysis. LRYGB was equal weight to LSG for diabetes (P-value=0.10, odd ratio, 1.24, 95%CI, 0.96-1.61, I2 for heterogeneity=30%, P-value for heterogeneity, 0.14), and obstructive sleep apnea (P-value=0.38, odd ratio, 0.79, 95%CI, 0.47-1.33, I2 for heterogeneity=0.0%, P-value for heterogeneity, 0.98). However, LRYGB was superior to LSG regarding hypertension (P-value=0.009, odd ratio, 1.55, 95%CI, 1.20-2.0, I2 for heterogeneity=0.0%, P-value for heterogeneity, 0.59), dyslipidemia (odd ratio, 2.18, 95%CI, 1.15-4.16, P-value for overall effect, 0.02), and GERD, (P-value=0.003, odd ratio, 3.16, 95%CI, 1.48-6.76. LRYGB was superior to LSG for gastroesophageal reflux, hypertension, and dyslipidemia remission. While the two procedures were equal regarding diabetes and obstructive sleep, further reviews comparing LSG, and one anastomosis gastric bypass are recommended.